Flow Characterization of Porous Ultra-High-Temperature Ceramics for Transpiration Cooling - Dataset - Ifti, H S; Hermann, T; McGilvray, M; Larrimbe, L; Hedgecock, R; Vandeperre, L (University of Oxford, 2022)
Porous ultra-high-temperature ceramics (UHTCs) are a candidate group of materials for transpiration cooling of hypersonic vehicles due to their exceptionally high melting point, typically above 3000 K. Their high operating temperature permits a higher amount of radiative cooling than that achievable with conventional materials, which reduces the required coolant mass flow rate to cool the surface. This work experimentally examines the internal and external flow behavior of porous UHTC made of zirconium diboride (ZrB2) for the purpose of transpiration cooling. A dedicated ISO standard permeability test rig was built. The outflow velocity distribution was acquired employing miniature hot-wire anemometry. The data obtained for the pressure loss across the porous samples agree with the Darcy–Forchheimer model for flow in porous media; respective Darcy and Forchheimer permeability coefficients are calculated and reported. Cleaning the surface of the samples using sandpaper or an ultrasonic bath raised the permeability coefficient by up to 19%. The outflow velocity maps exhibit a good flow uniformity with an average standard deviation of 25.1% with respect to the mean value. Individual jets are absent, and the velocity varies within the same order of magnitude.